2022
DOI: 10.3389/fneur.2022.1071237
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant brain functional network strength related to cognitive impairment in age-related hearing loss

Abstract: PurposeAge-related hearing loss (ARHL) is a major public issue that affects elderly adults. However, the neural substrates for the cognitive deficits in patients with ARHL need to be elucidated. This study aimed to explore the brain regions that show aberrant brain functional network strength related to cognitive impairment in patients with ARHL.MethodsA total of 27 patients with ARHL and 23 well-matched healthy controls were recruited for the present study. Each subject underwent pure-tone audiometry (PTA), M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Interestingly, the supramarginal gyrus is involved in brain functions of receiving auditory inputs and phonological processing and the volume of grey matter in the right supramarginal gyrus was negatively associated with HD 43 . Similarly, a case-control study found that age-related hearing loss patients had deceased connectivity in the bilateral supramarginal gyrus 44 . In previous studies, individuals with HD showed a decreased volume in superior temporal gyrus, transverse temporal gyrus, and posterior superior temporal gyrus 14,15,45 .…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, the supramarginal gyrus is involved in brain functions of receiving auditory inputs and phonological processing and the volume of grey matter in the right supramarginal gyrus was negatively associated with HD 43 . Similarly, a case-control study found that age-related hearing loss patients had deceased connectivity in the bilateral supramarginal gyrus 44 . In previous studies, individuals with HD showed a decreased volume in superior temporal gyrus, transverse temporal gyrus, and posterior superior temporal gyrus 14,15,45 .…”
Section: Discussionmentioning
confidence: 89%